MODEL EKONOMI PRODUKTIF MASYARAKAT PESISIR MELALUI PENGEMBANGAN WISATA BERBASIS KULINER (Studi Kasus Masyarakat Pesisir Pantai Tobilolong Kecamatan Kupang Barat Kabupaten Kupang) - Usman, Hapsa; DJunias, Donny, T. S; B. Bowakh, B. Bowakh (BISNIS, 2016)
In research was conductedin the District of West Kupang Tabilolong Village with the object of research is the economic potential and local culinary tourism. Methods of data collection through field survey, interviews, and question naires. Primary and secondary data sourcesof dataanalysistechniques qualitative descriptive approach SWOTanalysis. Research results show that excellent potential villagers Sea Tabilolong is the result in the form of fish and seaweed are abundant in number, and tourist beaches Tobilolong very potential to be developed with an average value of tourism potential Tablolong by 37 of 21 high-potential tourist factor.From the aspect of visitors average 56% of respondents did not agree with the conditions of the state of the object culinary tour today, while the level of interest of the tourists to the development of culinary travel an average of 89% so that thechances of developing a culinary tourism in coastal Tabilolong very promising it needs the development of culinary tourism Tabilolong Beach. Whereas the results of SWOT analysis showed some strength and weakness of the average value of IFAs by 2.56, with the weakness of the tourist Tobilolong is inadequate access to transportation, limited human resources, infrastructure is inadequate, the absence of tourist ecosystem maintenance, sanitation and hygiene the bad, and no eating it needs the attention of all parties. External analysis results (EFAS) with an average value was 2.17 higher opportunity andchance when compared to the threat level of 0.47. By chance culinary high tourism this it is necessary the development of economic culinary local attractions through.